Pengaruh Metode Pembelajaran Problem Solving terhadap Kemampuan Berfikir Kritis dan Motivasi Siswa Materi Perdagangan Internasional di MTSn 1 Kota Blitar - Dewi Sophia Ariani; Hendra Pratama (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2025)
This study aims to determine whether the problem solving method can improve critical thinking skills and motivation of class VII students at Mtsn 1 Kota Blitar. The researcher used a quantitative research method, using a control class and an experimental class. The study was conducted with 36 students in the control class and 38 students in the experimental class. The results of the T-Test on the critical thinking questionnaire showed that there was a significant difference between the problem solving learning model and students' critical thinking, this is evidenced by a significance value of 0.73. The decision of 0.73> 0.05 indicates that Ho is rejected and Ha is accepted, the results of the T-Test on the learning motivation questionnaire show that there is a significant difference between the problem solving learning model and students' learning motivation, this can be proven by a significance value of 0.001. The decision where 0.001> 0.05 indicates that H0 is rejected while Ha is accepted. The results of the T-Test on student learning outcomes obtained from the pre-test and post-test show that there is a significant influence between the problem solving learning model and student learning outcomes. This is proven by a significance value of 0.000. The decision where 0.000>0.05 indicates that H0 is rejected while Ha is accepted.